Examining Kumaoni women's experiences with colonialism in pre-Partition India: Unveiling forgotten narratives: Kumaoni women's struggle in colonial India (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The 'women's collection of experiences' as a topic has been in the middle phase of seriousresearch among western academics for the last many decades. Antiquarians have recently made an effortto highlight the significance of 'women' simply as half of the population, whose experiences have beenlargely left out of the formation of mankind's canon. In her first reading of the book, one researcheremphasises the fact that the topic of women has not been recognised until the recent past. He implies thatthe second half of the last century made significant progress towards what Carr has argued, namely,history as a discourse among many people over a long period of time that shapes the future. The firstgeneration of women's rights activists focused on equality and equality for women, while the secondwave fought against maltreatment of women. The third tidal surge highlighted internal fortification.